1986
DOI: 10.1159/000281183
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E<sub>2</sub> bei Prostatitis und Prostataadenom

Abstract: The measurement of prostaglandin E2 (PGE2) concentrations in the serum and prostatic fluid of healthy men, patients with prostatic hyperplasia and of patients with prostatitis was attempted and correlated to the state of disease, respectively. PGE2-concentrations with prostatic fluid of healthy men were found to be significantly lower than in patients with prostatitis. Corresponding to the course of treatment concentrations normalized, being favorably influenced by sitosterin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…It has been shown that the phytosterols, mainly β-sitosterol, possess anti-inflammatory activity and inhibit the stimulation and synthesis of prostaglandins, aromatase activity and 5α-reductase activity [131]. β-sitosterol reportedly helps in the reduction of high levels of prostaglandins in BPH patients [132] and suppresses prostatic growth factors and cholesterol accumulation. Phytosterols have also been reported to eliminate blood vessel congestion and excess blood and consequently, reduce the size of prostate adenomas.…”
Section: Plant-based Approach Employed In Bph and Pcmentioning
confidence: 99%
“…It has been shown that the phytosterols, mainly β-sitosterol, possess anti-inflammatory activity and inhibit the stimulation and synthesis of prostaglandins, aromatase activity and 5α-reductase activity [131]. β-sitosterol reportedly helps in the reduction of high levels of prostaglandins in BPH patients [132] and suppresses prostatic growth factors and cholesterol accumulation. Phytosterols have also been reported to eliminate blood vessel congestion and excess blood and consequently, reduce the size of prostate adenomas.…”
Section: Plant-based Approach Employed In Bph and Pcmentioning
confidence: 99%
“…Some of the cytokines, which have been reported to occur in elevated levels in Category III patients, are known to exert hyperalgesic effects, including TNFα, IL-1β, IL-6, and IL-8 [75,76]. High IL-1β in Category III CPPS also may be responsible for the stimulation of nociceptors through induction of prostaglandin synthesis [77] because prostaglandin E2 levels in the EPS of patients with chronic prostatitis were elevated compared with control subjects [78]. The detection of low expression of IL-10 in some patients with Category III CPPS [33] could additionally result in reduced antinociceptive effects [79].…”
Section: Consequencesmentioning
confidence: 99%
“…In non bacterial prostatitis the cultures are always negative in all four aliquots. Measurement of prostaglandin E2 con centration in prostatic fluid showed a significantly lower concentration in healthy men than in patients with pros tatitis [23], Prostatic biopsy unfortunately is not specifi cally diagnostic of (non)bacterial prostatitis [18]. Two studies, in which the patients had prostatic biopsies fol lowed by culturing for bacteria and for viruses, demon strated no etiologic role for such pathogens [24].…”
Section: Diagnostic Studiesmentioning
confidence: 99%